Studi Literatur : Potensi Pemanfaatan Zat Fitokimia Allicin bagi Tubuh - Nabila Juba Febrianti (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Allicin is an active compound found in garlic (Allium sativum). It gives garlic its distinctive aroma and flavor, and has powerful antimicrobial and antioxidant properties. Allicin is formed when garlic is sliced, cut, or crushed, when the enzyme alliinase reacts with the precursor compound alliin. This compound has a variety of health benefits. Allicin is an important component of garlic that is very effective in improving body health.